If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9 = 10 + -3(x + 1) + 11 Reorder the terms: -9 = 10 + -3(1 + x) + 11 -9 = 10 + (1 * -3 + x * -3) + 11 -9 = 10 + (-3 + -3x) + 11 Reorder the terms: -9 = 10 + -3 + 11 + -3x Combine like terms: 10 + -3 = 7 -9 = 7 + 11 + -3x Combine like terms: 7 + 11 = 18 -9 = 18 + -3x Solving -9 = 18 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -9 + 3x = 18 + -3x + 3x Combine like terms: -3x + 3x = 0 -9 + 3x = 18 + 0 -9 + 3x = 18 Add '9' to each side of the equation. -9 + 9 + 3x = 18 + 9 Combine like terms: -9 + 9 = 0 0 + 3x = 18 + 9 3x = 18 + 9 Combine like terms: 18 + 9 = 27 3x = 27 Divide each side by '3'. x = 9 Simplifying x = 9
| -(4y+3)-(-3y-8)=-3equation | | .25b=-5 | | -1/2=-6/18h | | X-3y=5.4 | | -2p+9=13 | | -6(1-2x)=-90 | | 5-3x=x+9 | | 5M+2=4M-1 | | 4.9=0.7m | | 8z+2z=9z+3 | | a+(a-32.5)+(a+23.4)=196.4 | | 14w-29=7w+20 | | -(4y+3)-(3y-8)=-3 | | 3y-4.2x=4.8x-6 | | 3(5x+4)+8x=-103 | | 4b+3=--9 | | -4=x+12 | | 11-6x-7-4x=6 | | 18/3.14=x | | -5=-a/56 | | -16=.50s-20 | | 4-4(6x-6)=172 | | 2(a-5)=3a-1 | | 3x^2-5x+2x=0 | | 4.5x+(-1.5y)=42 | | -9x+2=47 | | 2(4x+2)+5=33 | | C=18/3.14 | | .25z-9=1 | | v+(v-30.7)+(v+26.3)=195.7 | | 7=2-(8-1x) | | (a-5)=3a-1 |